2008
DOI: 10.1523/jneurosci.1129-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

The Basolateral Nucleus of the Amygdala Is Necessary to Induce the Opposing Effects of Stressful Experience on Learning in Males and Females

Abstract: The basolateral nucleus of the amygdala (BLA) has been implicated in the modulation of learning after stress. Acute inescapable stress enhances classical eyeblink conditioning in male rats, whereas the same stressor impairs eyeblink conditioning in female rats. The experiments here directly assessed whether inactivation of the BLA during stress exposure would block both the stress-induced facilitation in males and the retardation of eyeblink conditioning in females. To this end, the BLA was temporarily inactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 45 publications
4
67
0
Order By: Relevance
“…Daily corticosterone injections did not interfere with this task, indicating that corticosterone elevation per se cannot reproduce behavioral stress effects on behavioral flexibility. However, similar to previous stress-memory studies (Kim et al 2001;Waddell et al 2008), amygdalar inactivation during stress effectively blocked this effect. This suggests that the amygdala plays a crucial role in mediating stress effects across different cognitive domains.…”
supporting
confidence: 85%
“…Daily corticosterone injections did not interfere with this task, indicating that corticosterone elevation per se cannot reproduce behavioral stress effects on behavioral flexibility. However, similar to previous stress-memory studies (Kim et al 2001;Waddell et al 2008), amygdalar inactivation during stress effectively blocked this effect. This suggests that the amygdala plays a crucial role in mediating stress effects across different cognitive domains.…”
supporting
confidence: 85%
“…Animal studies also suggest that dimorphisms are implicated in gender differences of cerebral 5-HT levels in the hippocampus and amygdala (15) and the hippocampal 5-HT synthesis (16) is greater in female rats than in the males. Behavioral studies have shown differential sensitivities to various kinds of stresses such as novel environment in the open field test (17,18), swim stress (19), and eye-blink conditioning (20) between the males and females. These reports consistently indicate that the females exhibit less adaptation to acute stress.…”
Section: Metaplastic Regulation Of the Median Raphe Nucleus Via Serotmentioning
confidence: 99%
“…Furthermore, rapid spinogenesis of pyramidal neurons is induced by a single application of the synthetic glucocorticoid dexamethasone (Komatsuzaki et al, 2005) and NCAM and PSA-NCAM are known to be critically involved in regulating spinogenesis and synapatogenesis Muller et al, in press), as well as synaptic activity Cremer et al, 1998;LĂŒthi et al, 1994;Muller et al, 1996;Ronn et al, 1995;Senkov et al, 2006). Moreover, the basolateral amygdala (BLA) has been implicated in the facilitation of eyeblink conditioning induced by prior stress (Shors & Mathew, 1998;Waddell, Bangasser, & Shors, 2008) and recent evidence indicates that PSA-NCAM in this amygdaloid nucleus is highly responsive to different stress schedules (Cordero et al, 2005;Markram et al, 2007b). However, the potential implication of PSA-NCAM (and NCAM) in the amygdala on stress effects on conditioning processes still remains to be tested.…”
Section: Extrinsic Stress and Ncammentioning
confidence: 99%